Energy investigation on households with BIPV modules under net metering scheme - Kyritsis, Anastasios; Mathas, Vangelis; Tselepis, Stathis; Nikoletatos, John; Agathokleous, Rafaela; Kalogirou, Soteris A. (My University, 2017)
In recent years many Renewable Energy Sources (RES) power plants have been connected to power networks throughout Europe, in order to meet the EU’s objectives for sustainable energy supply. As far as low-voltage distribution networks are concerned, the grid-connected photovoltaic (PV) systems constitute the most important representative of RES, because these can be easily installed even in densely built-up areas where space problems are inevitable. In this context, small residential PV systems utilising BIPV modules are going to gain ground mainly at newly built or rebuilt building structures. That is because a BIPV module operates as a multi-functional building construction material; it generates energy and serves as part of the building envelope. This paper highlights the energy benefits of residential buildings in Southern Europe with BIPV modules under Net Metering Scheme. The energy benefits are reflected in monthly basis.
Keywords: Renewable energy sources; Grid-connected photovoltaic